PENGARUH KONSUMSI JANTUNG PISANG TERHADAP PRODUKSI ASI PADA IBU NIFAS - Ledy Octaviani Iqmy; Neneng Siti Lathifah (Universitas Jenderal Achmad Yani Yogyakarta, 2020)
Background: Increased breast milk production is affected by the presence of polyphenols and steroids in the heart of a banana.. Based on the results of the survey conducted by researchers at BPM Wirahayu Panjang in August 2018, of the 10 postpartum mothers, 6 (60%) of postpartum mothers whose less breast production and 4 (40%) postpartum mothers with smooth breastfeeding. While from the total postpartum mothers in August 2018, postpartum mothers who did not breastfeed were 14 people (33.3%) and only 28 people (66.6%) were breastfeeding.Objective: of this study was to determine the Effect of Banana Heart Consumption on Breast Milk Production in Postpartum Mothers Methods: This type of research uses quantitative research with a pre-experiment approach with the design of Two Group Pretest-Postest. Population is all postpartum mothers who delivered at BPM Wirahayu Panjang with an average birth rate in April-June 2019 of 120 people.The number of samples in this study with details of 30 case groups and 30 control groups. Result: it is known that the average milk production in the intervention group after consuming banana heart in postpartum mothers is 112,500 ml.Conclusion: influence of consumption of banana heart on breast milk production in BPM Wirahayu.